PENYAJIAN DAN KOMPONEN OTHER COMPREHENSIVE INCOME - Wahyu, Rima Putri Suryaning (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
Other Comprehensive Income is presented in three ways which are separated with from profit and loss report,combine with the profit and loss report and report the post of comprehensive profit posts in statement of changesin equity whereas in practice the Other Comprehensive Income are presented in the income of the period andcomprehensive income combined. The component of Other Comprehensive Income i.e. changes in revaluationsurplus, re-measurement on defined benefit program, the advantages and the disadvantages that arise from thedescription of financial statement from overseas business activities, re-measurement of financial asset which isâavailable for saleâ, and cash flow hedges.Keywords: Other Comprehensive Income, Comprehensive Profit and Loss Report, Statement of Changes inEquity.